UNIVERSITY STUDIES, ACCORDING TO ALUMNOS, DURING THE PANDEMIC. WHAT CHANGES ARE MAINTAINING REGARDING TEACHING METHODOLOGIES? - Hidalgo Izquierdo, Violeta (2024)
The article we present arises from research that studies the changes that occurred at the University, from the point of view of the students, regarding the teaching methodologies used by the professors. The year 2020 is the starting point of a new way of relating, because as a consequence of the confinement caused by the COVID-19 pandemic, social and work activity changed, and although it was temporary, it had its consequences that may have remained. Thus, in the different social environments, face-to-face activities began to be carried out remotely. At the University of Extremadura, this research team, as teachers, asked themselves what was happening in teaching, and above all, which of these changes remained with us. To do this, the opinions of the students of the University of Extremadura on the changes in teaching methodologies during confinement due to COVID-19 have been analyzed. The research method that has been used is the qualitative study of the answers given by the students to the open questions of the questionnaire validated by this research team. The results obtained indicate that the changes made in teaching methodologies during the COVID-19 pandemic are NOT perceived positively by students in their teaching/learning process. Consequently, it can be concluded that there is no manifestly clear unanimity among students regarding the positive and negative aspects obtained from this experience on the changes in teaching methodologies caused by the COVID-19 pandemic.